Designing properties of (Na1/2Bix)TiO3-based materials through A-site non-stoichiometry. Issue 4 (9th November 2017) - Frömling, Till; Steiner, Sebastian; Ayrikyan, Azatuhi; Bremecker, Daniel; Dürrschnabel, Michael; Molina-Luna, Leopoldo; Kleebe, Hans-Joachim; Hutter, Herbert; Webber, Kyle G.; Acosta, Matias
Abstract : Modification of microstructure and electrical properties due to high A-site diffusion of cations induced by non-stoichiometry during processing. Abstract : Point defects largely determine the properties of functional oxides. So far, limited knowledge exists on the impact of cation vacancies on electroceramics, especially in (Na1/2 Bi1/2 )TiO3 (NBT)-based materials. Here, we report on the drastic effect of A-site non-stoichiometry on the cation diffusion and functional properties in the representative ferroelectric (Na1/2 Bi1/2 )TiO3 –SrTiO3 (NBT–ST). Experiments on NBT/ST bilayers and NBT–ST with Bi non-stoichiometry reveal that Sr 2+ -diffusion is enhanced by up to six orders of magnitude along the grain boundaries in Bi-deficient material as compared to Bi-excess material with values of grain boundary diffusion ∼10 −8 cm 2 s −1 and ∼10 −13 cm 2 s −1 in the bulk. This also means a nine orders of magnitude higher diffusion coefficient compared to reports from other Sr-diffusion coefficients in ceramics. Bi-excess leads to the formation of a material with a core–shell microstructure. This results in 38% higher strain and one order of magnitude lower remanent polarization. In contrast, Bi-deficiency leads to a ceramic with a grain size six times larger than in the Bi-excess material and homogeneous distribution of compounds. Thus, the work sheds light on the rich opportunities that A-site stoichiometry offers to tailor NBT-based materials microstructure, transport properties, and electromechanical properties.